Analisis Implementasi Teknologi Blockchain dalam Meningkatkan Transparansi dan Kepercayaan di Sektor Keuangan di Indonesia - Wilson Wilson; Charles Yulian; Ricky Irwanto; Freddy Angtonius; Paulus Young Siahaan; Joosten Ng (International Forum of Researchers and Lecturers, 2024)
The background of this study is based on the challenges currently being faced by the Indonesian financial sector in terms of transparency and trust. Various cases that often occur such as data manipulation, fraud, and lack of accountability in the financial transaction process have drastically reduced public trust in financial institutions. Blockchain technology here is present as one of the potential solutions to overcome this problem, by offering a decentralized, transparent, and immutable financial recording system. This study aims to analyze the implementation of blockchain technology in increasing transparency and trust in the Indonesian financial sector. The research method used is qualitative with the Systematic Literature Review (SLR) approach. This research was conducted by collecting and analyzing relevant literature related to the implementation of blockchain in the financial sector, especially in Indonesia. The analysis process was carried out using the content analysis method in order to identify the benefits, challenges, and impacts of blockchain implementation on transparency and public trust. The results of the study show that blockchain has great potential in increasing transparency in the financial sector, by reducing the risk of data manipulation and increasing operational efficiency. However, several challenges are still faced, such as inadequate regulations, uneven technological infrastructure, and low digital literacy in the community. This study emphasizes the need for collaboration between the government, financial institutions, and the community to create an ecosystem that supports the widespread adoption of blockchain technology. With a collaborative approach, blockchain is expected to contribute significantly to strengthening a more transparent, accountable, and highly competitive financial ecosystem in the future. In addition, this study provides an understanding of the readiness of the Indonesian financial sector in facing technological changes and innovation opportunities in the future.